Signatures of positive selection in the mitochondrial genome of neotropical freshwater stingrays provide clues about the transition from saltwater to freshwater environment - Nachtigall, P. G.; Loboda, T. S.; Pinhal, D. [UNESP] (Springer Nature, 2023)
Neotropical freshwater stingrays (subfamily Potamotrygoninae) are carnivorous bottom feeder batoids widely distributed in most river basins of South America. They represent the unique extant group of elasmobranchs that evolved to live exclusively in freshwater environments. These species are exploited either by commercial fisheries (e.g., for food or ornamental industry) or by indigenous communities allocated along with their natural range. Restrictive life history characteristics coupled with habitat degradation make Potamotrygoninae species highly vulnerable to human impacts and highlight the necessity of studies to inform basic biological aspects, from ecology to genetics, to guide their conservation and clarify the molecular basis of adaptation to the freshwater environment. We used available and newly assembled Potamotrygon spp. mitogenomes to perform a comparative investigation of their molecular evolution. A phylogenetic estimation using the mitogenome of Potamotrygon falkneri and other Elasmobranchii supports monophyly for Potamotrygonidae and indicates a close relationship to Dasyatidae. A synteny analysis comprising 3 Potamotrygon and other 51 batoids revealed a highly conserved mitogenomic context. We detected various amino acid sites under positive selection exclusively in Potamotrygon spp., within the sequences of ND4, ND5, ND6, and COXII genes. Positively selected mutational events in key genes of energetic metabolism may be related to the physiological adaptation of Potamotrygon spp. during the ancient incursion into freshwater. This broad comparative mitogenomic study provides novel insights into the evolutionary history of neotropical freshwater stingrays and their relatives and stands out as a valuable resource to aid in current and future research on elasmobranch molecular evolution.
Keywords: Mitochondrial genome assembly; Molecular evolution; Phylogeny; Potamotrygonidae; RNA-seq